The female face of migration: unveiling the livelihood strategies and struggles of displaced syrian women - Dikmen, Mualla; Karatay, Abdullah (Acciones e Investigaciones Sociales, 2025)
This study explores the livelihood strategies, role transformations, and challenges experienced by Syrian refugee women in Turkey following forced migration. Using a qualitative phenomenological design, it captures women’s lived experiences while identifying structural and socio-cultural factors shaping their realities. Data were collected from 27 participants through semi-structured interviews, complemented by brief written reflections in which they listed their views immediately after the interview to refine thoughts and add insights that might not emerge in conversation. The interviews, conducted in Arabic with translator support, were transcribed verbatim and analysed using thematic analysis. To enhance interpretation, qualitative data were also “quantified” by calculating the frequency of recurring perceptions across the dataset. This approach highlighted prevalent themes while retaining narrative richness through selected quotations. Findings revealed that many participants, despite holding skilled occupations in Syria—such as lawyer, nurse, engineer, or teacher—shifted into informal, low-paid, or insecure work in Turkey, or remained unemployed. Structural barriers, including limited recognition of qualifications, bureaucratic obstacles to work permits, and labour market restrictions, hindered career continuity and reinforced economic precarity. Women also reported shifts in family livelihood roles, assuming greater economic responsibilities and reduced caregiving time, alongside multidimensional changes in economic, social, emotional, and cultural spheres. Reported challenges included low income, employment insecurity, lack of social networks, language barriers, and legal exclusion.  The findings contribute to literature on forced migration and gender, offering policy-relevant insights for inclusive, gender-sensitive integration strategies.
Keywords: Syrian refugee women; livelihood strategies; migration